Analysis Of The Needs Of Type A Terminal Infrastructure Facilities In Arjosari, Malang Based On Disaster Mitigation - Tri Wahyusetianingsih; Harris Muhammadun; Wateno Oetomo (Al-Makki Publisher, 2023)
A disaster is an event that can be predicted but cannot be known with certainty when it occurs. Recently, the intensity of natural disasters has increased, in the form of landslides, floods, earthquakes, tidal waves, typhoons, and volcanic eruptions. This needs to be watched out for everyone, including users of public facilities. Currently, there are not many public facilities that are friendly to disasters, one of which is the passenger terminal. This study aims to determine the potential vulnerability of terminal buildings and analyze the availability of terminal infrastructure facilities and the need for terminal infrastructure facilities based on disaster mitigation. The method used in the analysis of the needs of terminal infrastructure facilities is observation, interviews, and questionnaires, while to determine the potential vulnerability of terminal buildings using the Rapid Visual Screening (RVS) worksheet issued by FEMA 154-2015. Efforts made in mitigating disasters in terminal buildings are through structural mitigation by carrying out maintenance/rehabilitation of terminal buildings which include roof repairs, terminal runway repairs and repairs as well as the addition of evacuation signs.